Respuesta :
Answer:
1) [tex]x = -1[/tex] || 2) [tex]x = 10[/tex]
Explanation:
1)
→ [tex]\log _3\left(\frac{1}{3}\right)=x[/tex]
→ [tex]\frac{1}{3} = 3^x[/tex]
→ [tex]3^{-1} = 3^x[/tex]
→ [tex]x = -1[/tex]
2)
→ [tex]\log _3\left(x-1\right)=2[/tex]
→ [tex]x - 1 = 3^2[/tex]
→ [tex]x -1 = 9[/tex]
→ [tex]x = 9 +1[/tex]
→ [tex]x = 10[/tex]
[tex]\qquad \qquad\huge \underline{\boxed{\sf Answer}}[/tex]
Here's the solution ~
Question 1 :
[tex]\qquad \sf \dashrightarrow \: log_{ {3} }( \frac{1}{3} ) = x[/tex]
[tex]\qquad \sf \dashrightarrow \: log_{ {3} }( {3}^{ - 1} ) = x[/tex]
[tex]\qquad \sf \dashrightarrow \: log_{ {3} }( {3})^{ - 1 } = x[/tex]
[tex]\qquad \sf \dashrightarrow \: - 1 \times log_{3}(3) = x[/tex]
[tex]\qquad \sf \dashrightarrow \: - 1 \times 1 = x[/tex]
[tex]\qquad \sf \dashrightarrow \: x = - 1[/tex]
Question 2 :
[tex]\qquad \sf \dashrightarrow \: log_{3}(x - 1) = 2[/tex]
[tex]\qquad \sf \dashrightarrow \: x - 1 = {3}^{2} [/tex]
[tex]\qquad \sf \dashrightarrow \: x = 9 + 1[/tex]
[tex]\qquad \sf \dashrightarrow \: x = 10[/tex]